The The Effect Of Uncontrolled Addition Of Gelatin In Paracetamol Tablet Formulation And The Evaluation (Universitas Negeri Semarang, 2022)
Acetaminophen is a pain-relieving (analgesic) and fever-treating (antipyretic) medication that can be obtained over-the-counter. Wet granulation evaluation of granule among others flow time, angle of repose, tapped density tableting evaluation tablet among others weight uniformity, friability, disintegration time tablet flow time evaluation test was 0.16 with an angle of repose 51.78 tapped density of 30%. Tablet manufacturing process, tablet was damaged during the initial printing, namely capping. The tablet evaluation test obtained weight uniformity 248mg, friability 3.22%, disintegration time 1 minute, dissolution results at 60th minutes is 2.2817. The formulation of paracetamol tablets made by the researchers did not meet the specifications for marketability, where the discrepancy in tablet specifications occurred in the physical and chemical properties of the tablets.